DETERMINAN TIMELINESS OF FINANCIAL REPORTING PADA INDUSTRI MANUFAKTUR INDONESIA - mohamad zulman hakim (Universitas Muhammadiyah Tangerang, 2018)
This study aims to prove empirically the factors that affect the Timeliness of Financial Reporting. These factors are Return on Assets (ROA), Debt to Equity Ratio (DER), Company Size and Auditor Opinion as Independent Variables and Timeliness of Financial Statements as Dependent Variables.The population of this study is the Manufacturing Industry listed on the Indonesia Stock Exchange period 2012-2014. The sample was determined by purposive sampling method and 66 companies were obtained. The data used are obtained from the published company financial report. The method of analysis used is logistic regression at 5% significance level.Empirical study shows that ROA has significant effect on Timeliness of Financial Reporting. DER, Company Size and Auditor Opinion have no significant effect on Timeliness of Financial Reporting. Keywords: ROA, DER, Company Size, Auditor Opinion, Timeliness of Financial Reporting